The Knowledge Test Feedback Interventions (KTFI) increases knowledge level of spinal stenosis patients before surgery – A randomized controlled follow-up trial - Kesänen J; Leino-Kilpi H; Lund T; Montin L; Puukka P; Valkeapää K (ELSEVIER IRELAND LTD, 2022)
Objective
To assess the impact of a preoperative educational intervention on the knowledge level of patients with spinal stenosis.
Methods
One hundred spinal stenosis patients were randomized into a preoperative educational intervention group (IG, n = 50) or a control group (CG, n = 50). All the patients received routine preoperative education. In addition, the IG went through an empowering telephone discourse based on a knowledge test performed before admission to hospital. Data on patients’ knowledge level were collected at baseline (after the treatment decision), admission to hospital, discharge from hospital and at 3 and 6 months follow-up.
Results
At baseline, there was no difference in the knowledge level of the study groups. At admission, the knowledge level was significantly higher in five of six dimension of empowering knowledge in the IG compared to the CG. During follow-up, the knowledge level within the study groups remained stable.
Conclusion
A preoperative KTFI significantly increased the patients’ knowledge level in most dimensions of empowering knowledge.